Language and Migration in a Multilingual Metropolis : Berlin Lives - Stevenson, Patrick (Language and Globalization, 2017)
This lively and engaging book, set in the historical context of centuries of migration and multilingualism in Berlin, explores the relationship between language and migration. Berlin is a multicultural city in the heart of Europe, but what do we know about the number of languages spoken by its inhabitants and how they are used in everyday life? How do encounters with different languages impact on the experience of migration? And how do people use their experiences with language to shape their life stories? To investigate these questions, the author invites the reader to accompany him on a research expedition that leads to an apartment building in the highly diverse district of Neukölln. Its inhabitants come from different parts of the world and relate their experiences - their Berlin lives - in ways that reveal the complex and intricate relationships between language and migration.